A fly ash-based adsorbent and its preparation method and application

By preparing a fly ash-based adsorbent, the adsorbent significantly improves the adsorption capacity and fluorine removal rate of fluorine ions through ball milling and acid treatment of modified fly ash, and solves the problem of poor fluorine removal effect of fly ash-based adsorbent in the prior art.

CN119425647BActive Publication Date: 2025-04-08呼和浩特市生态环境监控中心

Patent Information

Application Number
CN202510018519.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-08
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing fly ash-based adsorbents have poor fluoride ions removal efficiency in wastewater treatment, and the fluorine removal rate is slow, making it difficult to meet the efficient and rapid fluorine removal needs.

Method used

A highly efficient fly ash based adsorbent is prepared by synergistically combining modified fly ash, modified lignin, activated carbon, polyethylene glycol polyvinyl alcohol graft copolymer, titanate and metal oxide. The adsorbent increases its specific surface area and active sites by ball milling and acid treatment of modified fly ash, and modifies the surface electrical properties of fly ash with cationic surfactant to improve fluorine ion adsorption efficiency.

Benefits of technology

The adsorption capacity and fluorine removal rate of fly ash-based adsorbents on fluorine ions can be significantly improved, and the fluorine ion concentration in the water sample can be significantly reduced in a short period of time, reaching the fluorine ion concentration limit requirement of Class V water quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a fly ash-based adsorbent and a preparation method and application thereof, and belongs to the technical field of adsorbent materials. The fly ash-based adsorbent comprises the following raw materials: modified fly ash, modified lignin, activated carbon, polyethylene glycol polyvinyl alcohol graft copolymer, titanate and metal oxide; wherein the fly ash is ball-milled, acid-modified and a surfactant is introduced to increase the adsorption sites and adsorption efficiency of the fly ash. The fly ash-based adsorbent prepared by the present invention through the synergistic effect between the raw materials can efficiently adsorb fluoride ions in wastewater, and the fluoride ion removal rate can reach 99% after adsorption for 30 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbent materials, and in particular relates to a fly ash-based adsorbent and a preparation method and application thereof. Background Art

[0002] Many industries produce fluoride-containing wastewater during the production process. The fluoride content in these wastewaters is often high, posing a serious threat to the environment and ecosystem. Fluoride-containing wastewater needs to go through a deep treatment process to ensure that it meets the requirements of effluent standards. With the intensification of industrial production, the discharge of high-concentration fluoride-containing industrial wastewater is also increasing, which puts higher requirements on wastewater treatment technology.

[0003] Fly ash is a solid waste generated in industrial processes such as coal-fired power plants. It is mainly composed of inorganic oxides, minerals and trace elements. Its particle shape is mostly micron-sized, with a large specific surface area and rich pore structure, which makes fly ash a potential excellent adsorption material. The application of fly ash in sewage treatment can achieve the effect of "waste treatment with waste", which will produce good economic and ecological benefits. At present, research on fly ash-based adsorbents in sewage treatment has made certain progress, but the fly ash-based adsorbents in the existing technology have poor fluoride ion removal efficiency and slow fluoride removal rate, which is difficult to meet the needs of efficient and rapid fluoride removal, and to a certain extent hinders the widespread promotion and application of fluoride removal technology. Therefore, it is urgent to develop new fly ash-based composite materials, and by combining with other functional materials, further improve the fluoride removal efficiency and stability of the adsorbent, and open up new ways for the efficient application of fly ash in sewage treatment. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention provides a fly ash-based adsorbent and a preparation method and application thereof, so as to solve the technical problems of poor defluorination effect and slow defluorination rate of fly ash-based adsorbent in the prior art.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is to provide a fly ash-based adsorbent, which includes the following raw materials in parts by weight: 50-70 parts of modified fly ash, 20-30 parts of modified lignin, 5-10 parts of activated carbon, 15-25 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 5-10 parts of titanate and 5-10 parts of metal oxide; the modified fly ash is prepared by the following method:

[0006] S1: ball milling the fly ash to obtain pretreated fly ash;

[0007] S2: adding the pretreated fly ash to an acid solution with a concentration of 0.1-1 mol / L, stirring at room temperature for 20-24 hours, and then washing and drying to obtain acid-treated fly ash;

[0008] S3: adding the acid-treated fly ash into the cationic surfactant solution, stirring at room temperature for 3-4 hours, then washing and drying to obtain;

[0009] The modified lignin is prepared by the following method: dissolving lignin in a solvent, then adding reduced graphene oxide, uniformly dispersing by ultrasonication, adding a cross-linking agent, and reacting at 40-60° C. for 3-6 hours to obtain the modified lignin.

[0010] Based on the above technical solution, the present invention can also be improved as follows.

[0011] Furthermore, the fly ash-based adsorbent comprises the following raw materials in parts by weight: 55-65 parts of modified fly ash, 22-28 parts of modified lignin, 6-9 parts of activated carbon, 17-22 parts of polyethylene glycol-polyvinyl alcohol graft copolymer, 6-9 parts of titanate and 6-9 parts of metal oxide.

[0012] Furthermore, the fly ash-based adsorbent comprises the following raw materials in parts by mass: 60 parts of modified fly ash, 25 parts of modified lignin, 8 parts of activated carbon, 20 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 8 parts of titanate and 8 parts of metal oxide; the metal oxide is aluminum oxide or iron oxide.

[0013] Furthermore, in step S1, the ball milling speed is 200-250 rpm, and the ball milling time is 10-20 min.

[0014] Furthermore, in step S2, the acid solution is a hydrochloric acid aqueous solution, a nitric acid aqueous solution or a sulfuric acid aqueous solution; and the material-liquid ratio of fly ash to the acid solution is 1 g: 8-10 mL.

[0015] Furthermore, in step S3, the solute of the cationic surfactant solution is hexadecyltrimethylammonium bromide or polydimethyldiallylammonium chloride, the solvent is water, the concentration of the cationic surfactant solution is 5-8wt%; and the solid-liquid ratio of fly ash to the cationic surfactant solution is 1g:8-10mL.

[0016] Furthermore, in steps S2 and S3, the washing method is to use deionized water to wash until the pH value of the washing solution is neutral; the drying temperature is 80-110° C., and the drying time is 2-3 hours.

[0017] Furthermore, the solvent is a mixed solvent consisting of anhydrous ethanol and solvent A; solvent A is dimethyl sulfoxide, N-methylpyrrolidone or N,N-dimethylformamide, and the volume ratio of anhydrous ethanol to solvent A is 1~1.5:1; the cross-linking agent is polyvinyl alcohol; the solid-liquid ratio of lignin, solvent, reduced graphene oxide and cross-linking agent is 10 mg: 0.1~0.2 mL: 20~30 mg: 5~8 mg; the ultrasonic time is 30~35 min, and the ultrasonic frequency is 35~45 kHz.

[0018] The invention also discloses a method for preparing the fly ash-based adsorbent, which comprises the following steps: uniformly mixing modified fly ash, modified lignin, activated carbon, polyethylene glycol polyvinyl alcohol graft copolymer, titanate and metal oxide and ball milling the mixture.

[0019] Furthermore, the ball milling speed is 800~1000r / min, and the ball milling time is 2~3h.

[0020] The invention also discloses the application of the fly ash-based adsorbent in the treatment of fluorine-containing wastewater.

[0021] The beneficial effects of the present invention are:

[0022] 1. The fly ash-based adsorbent of the present invention uses modified fly ash, modified lignin, activated carbon, polyethylene glycol polyvinyl alcohol graft copolymer, titanate and metal oxide as raw materials. Through the synergistic coordination of the raw materials, the prepared adsorbent has excellent adsorption capacity for fluoride ions;

[0023] 2. In the process of fly ash modification, fly ash is ball-milled to increase its specific surface area and provide more active sites. More hydroxyl groups are exposed on the surface of fly ash after acid treatment. Then cationic surfactants are introduced on the surface of fly ash. Cationic surfactants can react with exposed hydroxyl groups to form new adsorption sites. Adsorption sites can form more stable adsorption structures with fluoride ions. Secondly, cationic surfactants change the electrical properties of the fly ash surface, making it positively charged, making it easier to combine with fluoride ions through electrostatic attraction, thereby improving its adsorption efficiency. Through acid treatment and the reaction of cationic surfactants, the pore structure of fly ash may be improved, which is conducive to fluoride ions entering the fly ash particles more easily and interacting with the internal adsorption sites. Lignin not only provides adsorption sites with its own functional groups, but also significantly enhances its adsorption performance when combined with reduced graphene oxide. The large specific surface area and excellent electronic conductivity of reduced graphene oxide help accelerate the diffusion and adsorption process of fluoride ions on the surface of the adsorbent. Activated carbon has a high specific surface area and rich microporous structure. It is combined with other raw materials to further improve the overall adsorption performance. The introduction of polyethylene glycol polyvinyl alcohol graft copolymer can improve the hydrophilicity and chemical stability of fly ash-based adsorbents and enhance the performance of adsorbents in complex environments. Polyethylene glycol polyvinyl alcohol graft copolymers may also promote the diffusion and distribution of fluoride ions in the adsorbent during the adsorption process through their special molecular structure. The introduction of metal oxides (such as alumina) provides more active sites, which can undergo ion exchange with fluoride ions to improve adsorption efficiency. Titanate helps to improve the interfacial compatibility of various raw materials and enhance the structural stability of the adsorbent. The raw materials play a synergistic role in improving the adsorption efficiency and selectivity of the adsorbent for fluoride ions in wastewater. The modified lignin and polyethylene glycol polyvinyl alcohol graft copolymer in the raw materials are both bio-based materials, which help to enhance the eco-friendliness of the adsorbent. DETAILED DESCRIPTION

[0024] The raw materials used in the present invention: fly ash comes from Jinqiao Thermal Power Plant in Hohhot.

[0025] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0026] Example 1

[0027] A fly ash-based adsorbent comprises the following raw materials in parts by mass: 60 parts of modified fly ash, 25 parts of modified lignin, 8 parts of activated carbon, 20 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 8 parts of titanate and 8 parts of aluminum oxide.

[0028] The method for preparing modified fly ash in raw materials comprises the following steps:

[0029] S1: Place fly ash in a ball mill, add grinding balls at a ball-to-material ratio of 4:1, and mill for 15 minutes at a ball mill speed of 250 rpm to obtain pretreated fly ash;

[0030] S2: 20 g of pretreated fly ash was added to 200 mL of 0.5 mol / L hydrochloric acid aqueous solution, and stirred at room temperature for 24 h. The fly ash after the reaction was then washed with deionized water until the pH value of the washing solution was neutral. The fly ash was then dried at 100 ° C for 2 h to obtain acid-treated fly ash.

[0031] S3: Take 20g of acid-treated fly ash and add it to 200mL of 8wt% hexadecyltrimethylammonium bromide aqueous solution, and stir it at room temperature for 3h. Then wash the fly ash after the reaction with deionized water until the pH value of the washing liquid is neutral. Then dry the fly ash at 100℃ for 2h.

[0032] The method for preparing modified lignin in raw materials comprises the following steps:

[0033] Take 1g of lignin and dissolve it in 20mL of a mixed solvent of anhydrous ethanol and dimethyl sulfoxide, the volume ratio of anhydrous ethanol and dimethyl sulfoxide in the mixed solvent is 1:1, then add 2g of reduced graphene oxide to the solution, and then ultrasonicate it at an ultrasonic frequency of 40kHz for 30min to make it evenly dispersed, and then add 0.5g of polyvinyl alcohol to the dispersion, and stir the reaction at 50℃ for 4h to obtain the product.

[0034] The method for preparing the fly ash-based adsorbent comprises the following steps:

[0035] The modified fly ash, modified lignin, activated carbon, polyethylene glycol polyvinyl alcohol graft copolymer, titanate and alumina are mixed and ball-milled at a ball-milling speed of 900 r / min for 2 hours to obtain the product.

[0036] Example 2

[0037] A fly ash-based adsorbent comprises the following raw materials in parts by mass: 55 parts of modified fly ash, 22 parts of modified lignin, 6 parts of activated carbon, 25 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 6 parts of titanate and 6 parts of iron oxide.

[0038] The method for preparing modified fly ash in raw materials comprises the following steps:

[0039] S1: Place fly ash in a ball mill, add grinding balls at a ball-to-material ratio of 4:1, and mill at a ball mill speed of 250 rpm for 10 minutes to obtain pretreated fly ash;

[0040] S2: Take 20g of pretreated fly ash and add it to 160mL of 1mol / L nitric acid aqueous solution, and stir and react at room temperature for 20h, then wash the fly ash after the reaction with deionized water until the pH value of the washing liquid is neutral, and then dry the fly ash at 80℃ for 3h to obtain acid-treated fly ash;

[0041] S3: Take 20g of acid-treated fly ash and add it to 160mL of 5wt% hexadecyltrimethylammonium bromide aqueous solution, and stir it at room temperature for 4h. Then wash the fly ash after the reaction with deionized water until the pH value of the washing liquid is neutral. Then dry the fly ash at 80℃ for 3h.

[0042] The method for preparing modified lignin in raw materials comprises the following steps:

[0043] Take 1g of lignin and dissolve it in 20mL of a mixed solvent of anhydrous ethanol and dimethyl sulfoxide, the volume ratio of anhydrous ethanol and dimethyl sulfoxide in the mixed solvent is 1:1, then add 3g of reduced graphene oxide to the solution, and then ultrasonicate it at an ultrasonic frequency of 45kHz for 30min to make it evenly dispersed, and then add 0.8g of polyvinyl alcohol to the dispersion, and stir the reaction at 40℃ for 6h to obtain the product.

[0044] The method for preparing the fly ash-based adsorbent comprises the following steps:

[0045] The modified fly ash, modified lignin, activated carbon, polyethylene glycol polyvinyl alcohol graft copolymer, titanate and iron oxide are mixed and ball-milled at a ball-milling speed of 1000 r / min for 3 hours to obtain the product.

[0046] Example 3

[0047] A fly ash-based adsorbent comprises the following raw materials in parts by mass: 50 parts of modified fly ash, 28 parts of modified lignin, 5 parts of activated carbon, 17 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 5 parts of titanate and 5 parts of aluminum oxide.

[0048] The method for preparing modified fly ash in raw materials comprises the following steps:

[0049] S1: Place fly ash in a ball mill, add grinding balls at a ball-to-material ratio of 4:1, and mill at a ball mill speed of 200 rpm for 20 minutes to obtain pretreated fly ash;

[0050] S2: 20 g of pretreated fly ash was added to 200 mL of 0.1 mol / L sulfuric acid aqueous solution, and stirred at room temperature for 22 h. The fly ash after the reaction was then washed with deionized water until the pH value of the washing solution was neutral. The fly ash was then dried at 110° C. for 2 h to obtain acid-treated fly ash.

[0051] S3: Take 20g of acid-treated fly ash and add it to 200mL of 6wt% hexadecyltrimethylammonium bromide aqueous solution, and stir it at room temperature for 3h. Then wash the fly ash after the reaction with deionized water until the pH value of the washing liquid is neutral. Then dry the fly ash at 110℃ for 2h.

[0052] The method for preparing modified lignin in raw materials comprises the following steps:

[0053] Take 1g of lignin and dissolve it in 20mL of a mixed solvent of anhydrous ethanol and N-methylpyrrolidone, the volume ratio of anhydrous ethanol to N-methylpyrrolidone in the mixed solvent is 1.5:1, then add 2.5g of reduced graphene oxide to the solution, and then ultrasonicate it for 35min at an ultrasonic frequency of 35kHz to make it evenly dispersed, and then add 0.6g of polyvinyl alcohol to the dispersion, and stir the reaction at 60℃ for 3h to obtain the product.

[0054] The method for preparing the fly ash-based adsorbent comprises the following steps:

[0055] The modified fly ash, modified lignin, activated carbon, polyethylene glycol polyvinyl alcohol graft copolymer, titanate and alumina are mixed and ball-milled at a ball-milling speed of 800 r / min for 2 hours to obtain the product.

[0056] Example 4

[0057] A fly ash-based adsorbent comprises the following raw materials in parts by mass: 65 parts of modified fly ash, 20 parts of modified lignin, 9 parts of activated carbon, 15 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 9 parts of titanate and 9 parts of iron oxide.

[0058] The method for preparing modified fly ash in raw materials comprises the following steps:

[0059] S1: Place fly ash in a ball mill, add grinding balls at a ball-to-material ratio of 4:1, and mill for 18 minutes at a ball mill speed of 200 rpm to obtain pretreated fly ash;

[0060] S2: 20 g of pretreated fly ash was added to 200 mL of 0.5 mol / L hydrochloric acid aqueous solution, and stirred at room temperature for 22 h. The fly ash after the reaction was then washed with deionized water until the pH value of the washing solution was neutral. The fly ash was then dried at 100 ° C for 2 h to obtain acid-treated fly ash.

[0061] S3: Take 20g of acid-treated fly ash and add it to 200mL of 8wt% polydimethyldiallylammonium chloride aqueous solution, and stir it at room temperature for 4h. Then wash the fly ash after the reaction with deionized water until the pH value of the washing solution is neutral. Then dry the fly ash at 100℃ for 2h.

[0062] The method for preparing modified lignin in raw materials comprises the following steps:

[0063] Take 1g of lignin and dissolve it in 20mL of a mixed solvent of anhydrous ethanol and N,N-dimethylformamide, the volume ratio of anhydrous ethanol and N,N-dimethylformamide in the mixed solvent is 1:1, then add 2.5g of reduced graphene oxide to the solution, and then ultrasonicate it at an ultrasonic frequency of 35kHz for 35min to make it evenly dispersed, and then add 0.6g of polyvinyl alcohol to the dispersion, and stir the reaction at 50℃ for 5h to obtain the product.

[0064] The method for preparing the fly ash-based adsorbent comprises the following steps:

[0065] The modified fly ash, modified lignin, activated carbon, polyethylene glycol polyvinyl alcohol graft copolymer, titanate and iron oxide are mixed and ball-milled at a ball-milling speed of 800 r / min for 3 hours to obtain the product.

[0066] Example 5

[0067] A fly ash-based adsorbent comprises the following raw materials in parts by mass: 70 parts of modified fly ash, 30 parts of modified lignin, 10 parts of activated carbon, 22 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 10 parts of titanate and 10 parts of aluminum oxide.

[0068] The preparation method of the modified fly ash in the raw material is the same as that in Example 1.

[0069] The preparation method of the modified lignin in the raw material is the same as that in Example 1.

[0070] The preparation method of fly ash-based adsorbent is the same as that in Example 1.

[0071] Comparative Example 1

[0072] The difference from Example 1 is that the fly ash is not modified.

[0073] Comparative Example 2

[0074] The difference from Example 1 is that the lignin is not modified.

[0075] Comparative Example 3

[0076] The difference from Example 1 is that no polyethylene glycol polyvinyl alcohol graft copolymer is added.

[0077] Comparative Example 4

[0078] The difference from Example 1 is that no alumina was added.

[0079] Comparative Example 5

[0080] The difference from Example 1 is that the method for preparing modified fly ash in the raw material omits step S3.

[0081] Comparative Example 6

[0082] The difference from Example 1 is that no modified fly ash is added.

[0083] Experimental example

[0084] ① Prepare 1L of aqueous solution with a fluoride ion concentration of 10 mg / L and a pH value of 5 as simulated fluoride-containing wastewater, take 1g of the adsorbent prepared in Examples 1 to 5 and Comparative Examples 1 to 7 into the wastewater, and conduct adsorption tests at 40°C. Record the adsorption time, adsorption amount and solution fluoride ion concentration in detail, and then calculate the fluoride ion removal rate of the adsorbent according to the fluoride ion concentration in the water. The calculation results are shown in Table 1.

[0085] Table 1

[0086]

[0087] It can be seen from Table 1 that the adsorbent prepared in the embodiment has a better effect in removing fluoride ions from wastewater. In the preparation process of the fly ash-based adsorbent in Comparative Example 1, the fly ash was not modified, the pores of the fly ash were in a closed state, and the adsorption sites could not be exposed, resulting in a decrease in the adsorption capacity of the adsorbent; in the embodiment, the fly ash was first ball-milled to destroy the original structure of the fly ash, increase the specific surface area of ​​the fly ash, and expose the active groups; the acid treatment exposed more hydroxyl groups on the surface of the fly ash, and then the cationic surfactant could react with the exposed hydroxyl groups to form new adsorption sites, and the cationic surfactant changed the electrical properties of the fly ash surface, making it positively charged, making it easier to combine with fluoride ions through electrostatic attraction, further improving the adsorption efficiency. In Comparative Example 2, the lignin was not modified, the adsorption performance of the lignin was limited, and the adsorbent prepared using it also had poor adsorption performance; while the composite reduction of graphene oxide by lignin in the embodiment can significantly enhance its adsorption performance. In the comparative example, no polyethylene glycol polyvinyl alcohol graft copolymer, alumina and modified fly ash were added to the raw materials, and the adsorption performance of the prepared adsorbents was poor. In comparative example 5, no cationic surfactant was introduced on the surface of the fly ash after acid treatment, and the adsorption performance of the adsorbent prepared using this as raw material also deteriorated.

[0088] ② Take 1L of the original sewage sample from the sewage treatment plant, whose fluoride ion concentration is 9.87mg / L and pH value is 5.6, add 1g of the adsorbent prepared in Examples 1 to 5 to the water sample, stir at a low speed for 20min at a temperature of 25±2℃, and perform an adsorption experiment. Then, take the supernatant to determine the fluoride ion concentration therein, and calculate the removal efficiency of the adsorbent for fluoride ions based on this, and the results are shown in Table 2.

[0089] Table 2

[0090]

[0091] According to the fluoride ion concentration limit of Class V water quality specified in the "Surface Water Environmental Quality Standard" (GB3838-2002), it is 1.5 mg / L. It can be seen from Table 2 that the adsorbent prepared in the embodiment can significantly reduce the fluoride ion concentration in the water sample in a relatively short time, so that it meets the fluoride ion concentration limit requirement of Class V water quality.

[0092] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of the present invention. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still belong to the scope of protection of the present invention.

Claims

1. A fly ash-based adsorbent, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of modified fly ash, 20-30 parts of modified lignin, 5-10 parts of activated carbon, 15-25 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 5-10 parts of titanate and 5-10 parts of metal oxide; the metal oxide is aluminum oxide or iron oxide; the modified fly ash is prepared by the following method: S1: ball milling the fly ash to obtain pretreated fly ash; S2: adding the pretreated fly ash to an acid solution with a concentration of 0.1-1 mol / L, stirring at room temperature for 20-24 hours, and then washing and drying to obtain acid-treated fly ash; S3: adding the acid-treated fly ash into a cationic surfactant solution, stirring at room temperature for 3-4 hours, and then washing and drying to obtain; The modified lignin is prepared by the following method: dissolving lignin in a solvent, then adding reduced graphene oxide, uniformly dispersing by ultrasonication, adding a crosslinking agent, and reacting at 40-60° C. for 3-6 hours to obtain the modified lignin; The fly ash-based adsorbent is prepared by the following steps: modified fly ash, modified lignin, activated carbon, polyethylene glycol polyvinyl alcohol graft copolymer, titanate and metal oxide are mixed and ball-milled to obtain the adsorbent.

2. The fly ash-based adsorbent according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 55-65 parts of modified fly ash, 22-28 parts of modified lignin, 6-9 parts of activated carbon, 17-22 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 6-9 parts of titanate and 6-9 parts of metal oxide.

3. The fly ash-based adsorbent according to claim 2, characterized in that: The invention comprises the following raw materials in parts by weight: 60 parts of modified fly ash, 25 parts of modified lignin, 8 parts of activated carbon, 20 parts of polyethylene glycol polyvinyl alcohol graft copolymer, 8 parts of titanate and 8 parts of metal oxide.

4. The fly ash-based adsorbent according to claim 1, characterized in that: In step S1, the ball milling speed is 200-250 rpm, and the ball milling time is 10-20 min.

5. The fly ash-based adsorbent according to claim 1, characterized in that: The acid solution in step S2 is a hydrochloric acid aqueous solution, a nitric acid aqueous solution or a sulfuric acid aqueous solution; the material-liquid ratio of fly ash to the acid solution is 1g:8~10mL.

6. The fly ash-based adsorbent according to claim 1, characterized in that: The solute of the cationic surfactant solution in step S3 is hexadecyltrimethylammonium bromide or polydimethyldiallylammonium chloride, the solvent is water, the concentration of the cationic surfactant solution is 5-8wt%; the material-liquid ratio of fly ash to cationic surfactant solution is 1g:8-10mL.

7. The fly ash-based adsorbent according to claim 1, characterized in that: The washing method in steps S2 and S3 is to wash with deionized water until the pH value of the washing solution is neutral; the drying temperature is 80-110° C., and the drying time is 2-3 hours.

8. The fly ash-based adsorbent according to claim 1, characterized in that: The solvent is a mixed solvent consisting of anhydrous ethanol and solvent A; the solvent A is dimethyl sulfoxide, N-methylpyrrolidone or N,N-dimethylformamide, and the volume ratio of anhydrous ethanol to solvent A is 1-1.5:1; the cross-linking agent is polyvinyl alcohol; the solid-liquid ratio of lignin, solvent, reduced graphene oxide and cross-linking agent is 10 mg: 0.1-0.2 mL: 20-30 mg: 5-8 mg; the ultrasonic time is 30-35 min, and the ultrasonic frequency is 35-45 kHz.

9. Use of the fly ash-based adsorbent according to any one of claims 1 to 8 in the treatment of fluorine-containing wastewater.

Citation Information

Patent Citations

  • Fly ash-based heavy metal adsorbent and preparation method thereof

    CN104815621A

  • Preparation method for heavy metal ions absorbent

    CN106268663A

Cited By

  • Integrated preparation device based on ball-milled coal-based solid waste passivation material

    CN119909827A